Genotyping of Drought Tolerant Upland Land Races of Rice Using SDS-PAGE of Total Seed Storage Protein - Tripathy, S. K.; Dash, Sasmita (International Journal of Bio-resource and Stress Management, 2015)
A set of drought tolerant local land races of Odisha (India) including popular high yielding upland rice genotypes were characterized using total seed storage protein fingerprinting. 15 out of 19 scorable polypeptide bands with molecular weights ranging from 26.0 to 123.0 kD revealed wide polymorphism (78.94%) based on presence/absence of bands. Besides, the polypeptide markers differed in staining intensity, migration velocity and their frequency among the test genotypes. Seed protein profiles showed wide genetic variation among the tested materials, with similarity coefficients varying 0.47 to 1.00. Six test genotypes togatherly and four paired genotypes showed complete homozygosity (S.I.=100%) for seed storage protein profile. While, Khursudi (Av. S.I.=0.58) followed by Khandagiri (Av. S.I.=0.62) and Nagina 22 (Av. S.I.=0.69) had high genetic dissimilarity from most of the varieties. Cluster analysis revealed nine distinct groups of rice varieties at the similarity coefficient 0.91. Khursudi maintained high genetic distance from Bastul, Brahmanaki, Zhu 11-26 and Vandana. Whereas, N22 showed appreciable genetic dissimilarity from Khandagiri and Zhu 11-26. Besides, Khandagiri was shown to be genetically distant from Asumakunda, Brahmanaki, Hiran, Khursudi, N22, Padarabank, Anjali and Vandana. Khandagiri is a popular high yielding widely adaptable improved upland variety. Drought tolerance may be introgressed into Khandagiri using highly divergent drought tolerant donors e.g., N22, Khursudi, Vandana and Zhu 11-26 through recombination breeding. Besides, a few genotype-specific polypeptide bands are useful for genotype identification.